Contextual Political Interpretation of the Principles of State in the Qur’an - Abd Rahman Nasution; Mardian Idris Harahap; Dimas Ardi Dinata; Alfi Ramadhan; Rafiqhi Wijaya (Universitas Islam Negeri Sumatera Utara, 2026)
This article examines the interpretation of state-related verses in the Qur'an through a contextual approach to political tafsir. Using textual and contextual analytical methods on five selected verses (QS. An-nisa’: 59, QS. Asyu-‘ara: 38-39, QS. al-anfal: 46, QS. al-hujurat: 9-10, and QS. al-ma’idah: 44), this study demonstrates that the principles of statecraft in the Qur'an are not static but contain dynamic values that can be adapted across various historical and political contexts. Integrating the views of classical scholars (Ibn Kathir and al-Qurṭubiy) with contemporary interpretations by modern Muslim thinkers (Fazlur Rahman, Nasr Hamid Abu Zayd, Abdullah Saeed) offers a framework of political tafsir relevant to contemporary Muslim nations. The analysis reveals that the Qur'an emphasizes legitimate authority (wilāyah), consultation (shūrā), unity, the rule of law, and justice ('adl) as foundations of the statecraft system. This contextual approach avoids the pitfalls of uncontrolled liberalization by employing the methodological boundaries of Maqāṣid al-Sharī'ah, distinguishing between absolute substantial values (thawabit) and dynamic political instruments (mutaghayyirat). This framework enables Qur'anic statecraft principles to be adapted to modern political systems such as democracy and republicanism without compromising textual integrity.